STRATEGI PENINGKATAN KINERJA PEGAWAI PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN SUMBERREJO - Saputra, Rangga Eka; Samsudin, Acep (Jurnal Bisnis Indonesia, 2024)
This investigation aimed to discover the approaches utilized by leaders to improve employeeperformance at PT PLN (Persero) Sumberrejo Customer Service Unit. The study employedqualitative research methodologies, gathering information through direct interviews andobservations with the management team at PT PLN (Persero) Sumberrejo Customer ServiceUnit. The amassed data were subsequently assessed using SWOT analysis methods. Theresults unveiled that the internal factors exerting considerable impact were identified asStrengths, while significant external factors were acknowledged as Opportunities. Thesuggested tactic is the SO (Strengths - Opportunities) strategy, concentrating on maximizingexisting strengths and seizing available opportunities to address weaknesses.Keywords: Execution, Tactics, Personnel Management, Strategic Assessment.